Survei Cross-Sectional Online Untuk Menilai Vaksin Covid-19 Terkait Akseptabilitas, Pengetahuan dan Kesediaan Membayar di Kalangan Mahasiswa Kesehatan Masyarakat di Provinsi Sumatera Utara - Daniel Ginting; Nina Fentiana; Rahmat Alyakin Dachi (Universitas Batanghari Jambi, 2021)
The purpose of the study was to assess the Covid-19 vaccine related to acceptability, knowledge and willingness to pay among public health students in North Sumatra Province. The research design is an online cross-sectional survey using